2008
DOI: 10.1111/j.1365-2966.2008.13885.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the substellar temperature regime down to ∼550 K

Abstract: We report the discovery of three very late T dwarfs in the UKIRT Infrared Deep Sky Survey (UKIDSS) Third Data Release: ULAS J101721.40+011817.9 (ULAS1017), ULAS J123828.51+095351.3 (ULAS1238) and ULAS J133553.45+113005.2 (ULAS1335). We detail optical and near‐infrared (NIR) photometry for all three sources, and mid‐IR photometry for ULAS1335. We use NIR spectra of each source to assign spectral types T8p (ULAS1017), T8.5 (ULAS1238) and T9 (ULAS1335) to these objects. ULAS1017 is classed as a peculiar T8 (T8p) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
149
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(156 citation statements)
references
References 37 publications
5
149
2
Order By: Relevance
“…Y-dwarfs definitively enter the realm of exoplanets. This is even more clear in figure 3 (from (Burningham et al (2008))), here the dark line spectrum is that of Jupiter, those bellow correspond to different Y-dwarfs, it is clear that the overall spectral shape of Y-dwarfs and Jupiter is remarkably similar.…”
Section: Brown Dwarfsmentioning
confidence: 53%
See 2 more Smart Citations
“…Y-dwarfs definitively enter the realm of exoplanets. This is even more clear in figure 3 (from (Burningham et al (2008))), here the dark line spectrum is that of Jupiter, those bellow correspond to different Y-dwarfs, it is clear that the overall spectral shape of Y-dwarfs and Jupiter is remarkably similar.…”
Section: Brown Dwarfsmentioning
confidence: 53%
“…BDs are believed to form the same way stars do, that is by the collapse of a dense core in a giant 52 M. T. Ruiz and that of four Y-dwarfs, is clear from this figure taken from (Burningham et al (2008)). molecular cloud, therefore, its metallicity should reflect that of the parent cloud.…”
Section: Brown Dwarfsmentioning
confidence: 76%
See 1 more Smart Citation
“…Spectral standards are those adopted for optical classification up to spectral class L8, and for near-IR classification for L9 and later. Near-IR spectral standards for earlier types can be found in Kirkpatrick et al (2010) (Warren et al 2007;Delorme et al 2008b;Burningham et al 2008). Lucas et al (2010) reported the discovery of an even cooler object UGPS 0722−05 which they suggested should be classified as T10, and could in the future be regarded as the first example of a new spectral type.…”
Section: Y Dwarfsmentioning
confidence: 99%
“…Two new classes have been added to the spectral type sequence following M: L and T. T dwarfs with effective temperatures (T eff ) as low as ∼500 K are now known (Warren et al 2007; Burningham et al 2008; Delorme et al 2008; Leggett et al 2009) and we are truly finding objects that provide the link between the low-mass stars and the giant planets.…”
Section: Introductionmentioning
confidence: 99%